Do Red Knots (Calidris Canutus Islandica) routinely skip Iceland during southward migration? - M Dietz; B Spaans; A Dekinga; Marcel Klaassen; H Korthals; C van Leeuwen; T Piersma (2010)
Subspecies Calidris canutus islandica of the Red Knot breeds on the arctic tundra of northeastern Canada and northern Greenland and winters along the coasts of northwestern Europe. During northward migration, it stops over in either Iceland or northern Norway. It has been assumed that it does the same during southward migration. Using ratios of stable carbon isotopes (δ 13 C) in whole blood, blood cells, and plasma, we investigated evidence for a stopover in Iceland en route from the breeding grounds to the Dutch Wadden Sea. With the expected diet (shellfish) and stopover duration at Iceland (12-15 days, maximum 17 days) and the turnover rates of blood cells (15.1 days) and plasma (6.0 days), Red Knots that stopped in Iceland should arrive with a blood (cell) δ 13 C midway between a tundra (-24.7[per thousand]) and a marine value (-14.0[per thousand]) and a plasma δ 13 C approaching the marine value (-15.3[per thousand]). However, many adults arriving at the Wadden Sea had δ 13 C ratios in blood (cells) and plasma below these levels, and some arrived with clear tundra signals in blood cells, suggesting that they skipped Iceland during southward migration. Surprisingly, available data suggest this also to be true for juveniles during their first southward migration. The δ 13 C signature of second-year birds confirmed that they oversummered in the Wadden Sea. Our findings contradict the largely untested idea that juvenile shorebirds make more stopovers than adults as well as the idea that the migration between the Nearctic and Europe is necessarily a two-leg process.